Impairment of endoplasmic reticulum is involved in β-cell dysfunction induced by microcystin-LR. (April 2017) - Zhao, Yanyan; Cao, Qing; He, Yaojia; Xue, Qingju; Xie, Liqiang; Yan, Yunjun
Abstract: Microcystins (MCs) widely distributed in freshwaters have posed a significant risk to human health. Previous studies have demonstrated that exposure to MC-LR impairs pancreatic islet function, however, the underlying mechanisms still remain unclear. In the present study, we explored the role of endoplasmic reticulum (ER) impairment in β-cell dysfunction caused by MC-LR. The result showed that MC-LR modified ER morphology evidenced by increased ER amount and size at low doses (15, 30 or 60 μM) and vacuolar and dilated ER ultrastructure at high doses (100 or 200 μM). Also, insulin content showed increased at 15 or 30 μM but declined at 60, 100, or 200 μM, which was highly accordant with ER morphological alteration. Transcriptomic analysis identified a number of factors and several pathways associated with ER protein processing, ER stress, apoptosis, and diabetes mellitus in the cells treated with MC-LR compared with non-treated cells. Furthermore, MC-LR-induced ER stress significantly promoted the expression of PERK/eIF2α and their downstream targets (ATF4, CHOP, and Gadd34), which indicates that PERK-eIF2α-ATF4 pathway is involved in MC-LR-induced insulin deficiency. These results suggest that ER impairment is an important contributor to MC-LR-caused β-cell failure and provide a new insight into the association between MCs contamination and the occurrence of human diseases. Graphical abstract: Highlights: MC-LR exposure alters ER morphology and insulin content in β-cells. Genes related to ER stress-mediated apoptosis were identified after MC exposure. PERK-eIF2α-ATF4 pathway are involved in β-cell dysfunction induced by MC-LR.